A comprehensive review of cardiotoxic effects of selected plants. (2nd October 2021) - Anaeigoudari, Akbar; Azdaki, Nahid; Khazdair, Mohammad Reza
Abstract: Some plants that were frequently grown in public city areas showed cardiotoxicity effects. The data of this review article were obtained from MEDLINE/PubMed, Scopus and Google Scholar until December 2019. The following keywords Aconitum, Datura stramonium, Nerium oleander, and cardiotoxicity were used. The toxic effects of plants induce changes in hematological indicators such as red blood cell and white blood cell, varying degrees of hemorrhage, myocardial degeneration and necrosis. They also lowered systolic blood pressure and induced bradycardia and tachycardia in some cases, reduce blood pressure and increased pulse rate. These plants induced hematological and electrolyte changes, arrhythmia induction, sinus bradycardia, prolonged P–R and QRS interval, electrocardiographic and pathological changes in the heart.